The economic revenues and the emergy costs of cruise tourism. (10th November 2017) - Paoli, C.; Vassallo, P.; Dapueto, G.; Fanciulli, G.; Massa, F.; Venturini, S.; Povero, P.
Abstract: Emergy analysis was applied to three municipalities (Portofino, Santa Margherita Ligure and Rapallo) of the Liguria Region coast, where tourism and cruise tourism are thriving. The results were compared with traditional economic indices. The territorial assessment of the municipalities was analysed by comparing the environmental costs with the economic benefits, focusing on tourism and cruise tourism. Similarities and differences among the case studies emerged. The three economies resulted as being driven by the tertiary sector, but consequences from the different development strategies came to light. Portofino has developed an elite type of tourism with greater attention devoted to the environment. This is mirrored by a sort of safeguarding of tourism and natural resources and by the detriment of the productive sector's success, on the contrary, in Rapallo. Santa Margherita lies in a boundary condition. The cruise tourism sector was analysed in these contexts. The ecological and economic impacts of the cruise sector were revealed to be significant only in Portofino, being less than 1% in Rapallo and Santa Margherita Ligure. The load imposed on the local environment by cruise ship tourism was calculated, and Portofino showed a limited condition, while Santa Margherita Ligure and Rapallo exceeded the local carrying capacity. This is due to the different management approaches pursued: only in Portofino is the territory more able to absorb the impact, although the limit is currently reached. As a consequence it appears to be evident that such phenomena as cruise tourism, albeit economically promising in the short term, should be managed with a long-term perspective, integrating them into the local context and setting up strategies for impact reduction or mitigation. Highlights: Cruise ships tourism was analyzed and evaluated in the context of local territory. Environmental costs and economic benefits of tourism and cruise sectors of three coastal municipalities were compared. Emergy analysis was applied aiming to a system approach able to translate results in monetary units. A carrying capacity index was calculated in order to evaluate if nature is able to absorb emissions from cruise tourism.